Encoding Race, Encoding Class : Indian IT Workers in Berlin - Amrute, Sareeta Bipin (Book collections on Project MUSE., 2016)
In Encoding Race, Encoding Class Sareeta Amrute explores the lives of Indian IT coders temporarily working in Berlin, showing how their cognitive labor reimagines race and class and how their acceptance and resistance to their work offers new potentials for alternative visions of living and working in neoliberal economies.